2022
DOI: 10.1002/chem.202201378
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Borane, NH3BH3: A Threshold Photoelectron–Photoion Coincidence Study of a Potential Hydrogen‐Storage Material

Abstract: We have investigated the photoionization of ammonia borane (AB) and determined adiabatic ionization energy to be 9.26 � 0.03 eV for the X + 2 E ! X 1 A 1 transition. Although the threshold photoelectron spectrum appears at first glance to be similar to the one of the isosteric ethane, the electronic situation differs markedly, due to different orbital energies. In addition, an appearance energy AE 0K -(NH 3 BH 3 , NH 3 BH 2 + ) = 10.00 � 0.03 eV has been determined, corresponding to the loss of a hydrogen atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 56 publications
8
10
0
Order By: Relevance
“…This is confirmed by a measurement using photoelectron–photoion coincidence (PEPICO) spectroscopy of and AIE of 9.26 ± 0.03 eV and an VIE of 10.00 ± 0.03 eV . The present calculated VIE of AB at 10.57 eV agrees well with the measurements which are between the two experimental measurements of 10.58 eV and 10.00 eV . In addition, our recent joint XPS experimental and theory study of hydroxybenzoic acids revealed that the vibrational impact is small for fast ionization processes so that in the present study, only the first-order VIEs are considered.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This is confirmed by a measurement using photoelectron–photoion coincidence (PEPICO) spectroscopy of and AIE of 9.26 ± 0.03 eV and an VIE of 10.00 ± 0.03 eV . The present calculated VIE of AB at 10.57 eV agrees well with the measurements which are between the two experimental measurements of 10.58 eV and 10.00 eV . In addition, our recent joint XPS experimental and theory study of hydroxybenzoic acids revealed that the vibrational impact is small for fast ionization processes so that in the present study, only the first-order VIEs are considered.…”
Section: Resultssupporting
confidence: 90%
“…It is noted that the VIE and AIE of ammonia borane (H 3 BNH 3 ) can differ by as much as approximately ∼1 eV, as the structures of the cation and neutral AB can be quite different. This is confirmed by a measurement using photoelectron–photoion coincidence (PEPICO) spectroscopy of and AIE of 9.26 ± 0.03 eV and an VIE of 10.00 ± 0.03 eV . The present calculated VIE of AB at 10.57 eV agrees well with the measurements which are between the two experimental measurements of 10.58 eV and 10.00 eV .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Schleier et al 2 reported that the first ionic state of AB (X state) supported vibronic structure, implying that this ionic state is bound. Here, we have shown that the A state also supports vibronic structure.…”
Section: Discussionmentioning
confidence: 99%